Phospholipase D- and phosphatidic acid-mediated signaling in plants - Li, M.; Hong, Y.; Wang, X.
The phospholipase D (PLD)family in higher plants is composed of multiple members, and each of the Arabidopsis PLDs characterized displays distinguishable properties in activity regulation and/or lipid preferences. The molecular and biochemical heterogeneities of the plant PLDs play important roles in the timing, location, and amount of phosphatidic acid (PA)produced. PLD-catalyzed production of PA has been shown to play important roles in plant growth, development, and response to various stresses, including drought, salinity, freezing, and nutrient deficiency. PLD and PA affect cellular processes through different modes of action, including direct target protein binding and biophysical effects on cell membranes. Improved knowledge on the mechanism by which specific PLDs and PA mediate given plant responses will facilitate the understanding of the molecular processes that connect the stimulus perception on membranes to intracellular actions and physiological responses.
Keywords: PHOSPHATIDIC ACID; PHOSPHOLIPASE D; LIPID SIGNALING; ABSCISIC ACID; N SIGNALING; HYPEROSMOTIC STRESS; ARABIDOPSIS; DROUGHT; G PROTEINS; PROTEIN KINASE; PROTEIN PHOSPHATASE